A Retrospective Study on Immediate Placement of Neoss Implants with Early Loading of Full‐Arch Bridges. (3rd December 2013) - Andersson, Peter; Degasperi, Werner; Verrocchi, Damiano; Sennerby, Lars
Abstract Background Full‐arch clearances of compromised teeth and placement of implant‐supported prostheses is one solution for the prosthetic rehabilitation of partially dentate patients. Purpose To retrospectively evaluate treatment outcomes after full clearance, immediate placement, and early loading of full‐arch fixed bridges. Materials and Methods Fifty‐five patients subjected to full clearance and placement of 284 Neoss implants (Bimodal™ and Proactive™, Neoss Ltd, Harrogate, UK) in 29 edentulous maxillae and 26 mandibles for early loading (1 to 3 days) of a provisional full‐arch bridge were retrospectively evaluated after 1 to 6 years of loading. Osstell™ measurements (Osstell AB, Göteborg, Sweden) were taken at placement and after 3 to 9 months when the provisional bridge was replaced with a permanent one. Marginal bone levels were measured in intraoral radiographs. Results All patients (100%) wore a fixed bridge at the time of finalizing the study. A total of 18 failures (6.3%) were encountered during the follow‐up, giving an overall cumulative survival rate of 93.7%. All failures occurred in the maxilla (10.6%), and no implants were lost in the mandible. More Bimodal™ (9.0%) than Proactive™ (4.1%) implants failed. Failing implants showed a significantly lower mean primary stability than successful ones (p = .015). Failed cases showed a significantly lower average ISQ for all implants (p = .015) and a marked decrease to the second registration, while successful cases showed and maintained high ISQs. The average bone loss after 1 year was 0.8 ± 0.5 mm. Conclusions Full‐arch clearance of severely diseased teeth followed by immediate placement of Neoss implants, early loading with provisional full‐arch bridges, and subsequent permanent bridges is a possible treatment modality for partially dentate patients. Caution with this approach is recommended for the maxilla, as opposed to the mandible.